2017
DOI: 10.1002/etc.3853
|View full text |Cite
|
Sign up to set email alerts
|

Hazard assessment of nickel nanoparticles in soil—The use of a full life cycle test with Enchytraeus crypticus

Abstract: Nanoparticles (NPs) such as nickel (Ni) are widely used in several applications. Nevertheless, the environmental effects of Ni NPs are still poorly understood. In the present study, the toxicity of Ni NPs and nickel nitrate (NiNO ) was assessed using the standard test species in soil ecotoxicology, Enchytraeus crypticus (Oligochaeta), in a full life cycle test, adding the endpoints hatching, growth, and time to reach maturity, besides survival and reproduction as in the standard Organisation for Economic Co-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 43 publications
6
20
0
Order By: Relevance
“…A nonmonotone dose response has been reported before for Ag 26 and Ni. 43 This could be related to the potentially reduced agglomeration at lower concentrations hence higher exposure and effects. However, we do not have evidence to support this hypothesis for the FP with or without embedded ENMs.…”
Section: ■ Ecotoxicity Effect Characterizationmentioning
confidence: 99%
“…A nonmonotone dose response has been reported before for Ag 26 and Ni. 43 This could be related to the potentially reduced agglomeration at lower concentrations hence higher exposure and effects. However, we do not have evidence to support this hypothesis for the FP with or without embedded ENMs.…”
Section: ■ Ecotoxicity Effect Characterizationmentioning
confidence: 99%
“…This is not always the case but it has been observed before for E. crypticus , e.g., when exposed to silver nitrate and silver nanoparticles [24]. On the other hand, exposure to copper oxide nanomaterials [25] or nickel nanoparticles [26] showed that the observed decreased hatching was in fact a delay, and organisms recovered with time. Similarly, the observed reduction in hatching at 5 and 1000 mg rGO/kg was partly a delay and effects were diluted with time, as observed in terms of survival and reproduction.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of MPs and NPs in soil aggregates can alter biological, chemical and physical properties of soil [85][86][87][88], and affect the estimation of soil carbon sequestration [89]. The effect of plastics on soil aggregate formation and humic acids properties are shown in Figure 3.…”
Section: Soil Chemical-physical Propertiesmentioning
confidence: 99%
“…Indeed, MPs and NPs can interact not only with soil-dwelling invertebrates but also with other organisms, such as terrestrial fungi and plant pollinators, which are involved in essential ecosystem services and functions [81]. However, the negative effects of NPs on the annelid worm, Enchytraeus crypticus, were lower than those due to other nanomaterials [89,[133][134][135]. Not only microorganisms but also molecules adsorbed by plastics affect the interactions between plastics and soil biota.…”
Section: Soil Faunamentioning
confidence: 99%